Women Researching in Africa The Impact of Gender - Jackson, Ruth.; Kelly, Max.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This edited collection explores the lives, consequences and motivations of female researchers in Africa, giving unprecedented insights into how their gender-and sometimes their ethnicity and age-impacted on their research experiences, and how doing research in Africa affected them as women. Each contributor considers her place or position in the research process and provides a vivid portrait of that experience. Drawing on research findings from Nigeria, Ethiopia, Cameroon, Ghana, Guinea, Malawi, Uganda and other African countries, the book looks at gender and identity as a female researcher in Africa; relationships with 'others'; and unique methodological challenges for female researchers in Africa. With refreshing candour, each chapter challenges other researchers in Africa (both women and men), to integrate critical reflections of gender and diverse gendered field experiences into their work. Women Researching in Africa will be of interest to students and scholars across a range of disciplines including development studies, anthropology, geography, gender studies and international studies.
1. Women researching in Africa: The impact of gender; Ruth Jackson and Max Kelly -- Part I: Gender and identity as a female researcher in Africa -- 2. ''Gone native?': Reflections of a feminist tightrope walker's research on 'land grabbing' and the dilemmas of 'fieldworking' while parenting; Rama Salla Dieng -- 3. Identity and experience in Malawi: Challenges and observations; Joanna Woods -- 4. Navigating gender performance: Ethics and culture in researching family care for cancer patients in Ghana; Deborah Atobrah -- 5. When in Rome...: Navigating decolonial research as a diasporic Black woman; Lioba Hirsch -- 6. Reflections on the dilemmas of feminist fieldwork in Africa; Tanya Lyons -- Part II: Relationships with 'others' as a female researcher in Africa -- 7. Researching the rural: A Mzungu loose in Africa; Max Kelly- 8. Women and anthropologists in West Africa: comparing two research experiences; Ester Botta Somparé and Mara Vitale -- 9. Constant questioning on-and-off the page: Race, decolonial ethics and women researching in Africa; Amber Murrey; 10. Lessons Learned on Research Methods and Researcher Stance in Africa; Jody L. McBrien -- Part III: Methodological challenges for female researchers in Africa -- 11. Challenges and opportunities of doing fieldwork as a woman on women in Guinea; Carole Ammann -- 12. On walking alone and walking with others: Framing activities and decisions by time and distance in Kafa Zone, Ethiopia; Ruth Jackson -- 13. Gender and positionality: Opportunities, challenges and ethical dilemmas in Ghana and Sierra Leone; Vanessa van den Boogaard -- 14. Historiography of African Market Women; Mutiat Oladejo -- 15. Women researching Africa: linking experience to practice; Max Kelly and Ruth Jackson. .
Keywords: Sex; Ethnology; Economic development; Gender Studies; Sociocultural Anthropology; Development Studies